2019
DOI: 10.1108/md-05-2018-0557
|View full text |Cite
|
Sign up to set email alerts
|

Does organizational culture matter in the relationship between trust and SMEs performance

Abstract: Purpose Although literature indicated that business social responsibility (BSR) is now a common practice and accepted norm among business enterprises globally, the concept is not well understood and its influence on business performance is contradictory. Therefore, based on the stakeholder theory, the purpose of this paper is to examine the association among trust of BSR and the performance of small-scale industries in Nigeria with organizational culture as a moderating factor. Design/methodology/approach Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 92 publications
0
39
0
2
Order By: Relevance
“…Malaysian SMEs faces issues regarding innovative culture and organizational learning (Abdul-Halim, Ahmad, Geare, & Thurasamy, 2018;Gorondutse & Hilman, 2018;Hanifah, Halim, Ahmad, & Vafaei-Zadeh, 2017). Moreover, Malaysian government plans to renovate their economy by adopting innovative culture and organizational learning among SMEs (Abdul-Halim et al, 2018;Hanifah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Malaysian SMEs faces issues regarding innovative culture and organizational learning (Abdul-Halim, Ahmad, Geare, & Thurasamy, 2018;Gorondutse & Hilman, 2018;Hanifah, Halim, Ahmad, & Vafaei-Zadeh, 2017). Moreover, Malaysian government plans to renovate their economy by adopting innovative culture and organizational learning among SMEs (Abdul-Halim et al, 2018;Hanifah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Clearly, this is not to overlook the fact that sustainability may also be linked to issues of, for instance, durability or continuity; nevertheless, increasing particular attention is required in relation to (environmental) sustainability especially in small-to-medium-sized enterprises [SMEs] (Kraus et al, 2020, Spence, 2016Wickert et al, 2016). Likewise, (Gorondutse, & Hilman, 2019) have established that there was a strong positive impact of organizational culture on the performance of the small-scale industries. However, (Dzomonda, & Fatoki, 2019) found that small and medium enterprises (SMEs) had an average level of entrepreneurial orientation (EO) as well an average level of organisational culture.…”
Section: Introductionmentioning
confidence: 99%
“…Globalization has brought many challenges to organizations in managing employee performance to achieve organizational goals (Gorondutse & Hilman, 2019;Polychroniou & Trivellas, 2018). The success of an organization hang on the utilization of human resources such as people who provide energy, creativity, and enthusiasm for the organization and plays a pivotal role in the implementation of organizational operations (Ali Alsheikh, Ahmad Alremawi, & Bin A Tambi, 2018).…”
Section: Introductionmentioning
confidence: 99%